1966
DOI: 10.1007/bf00390130
|View full text |Cite
|
Sign up to set email alerts
|

Production of gibberellin-like substance in the embryo of barley during germination

Abstract: Embryos were excised from barley seeds, their homogenates were incubated with ficin, and their content in gibberellin-like substance was assayed by means of α-amylase-producing activity, but no gibberellin-like substance could be detected.Embryos free from endosperm which were cultured for five days produced measurable amounts of gibberellin-like substance. This substance was not produced when a carbon source was absent from the medium, or when air was removed after 2 days of aerobic culture. CCC and Phosfon D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The embryo secretes gibberellin (13,34,44), and it has been shown that exogeneously applied gibberellic acid causes considerable ultrastructural changes in aleurone cells (32,33). This discovery led to a large number of investigations concerning the mode of action of gibberellic acid on isolated aleurone layers, and the capability of aleurone cells to produce enzymes necessary for the degradation of the endosperm in the seed is now well established (5,15,17,19,20,21,23,39,40).…”
Section: Introductionmentioning
confidence: 99%
“…The embryo secretes gibberellin (13,34,44), and it has been shown that exogeneously applied gibberellic acid causes considerable ultrastructural changes in aleurone cells (32,33). This discovery led to a large number of investigations concerning the mode of action of gibberellic acid on isolated aleurone layers, and the capability of aleurone cells to produce enzymes necessary for the degradation of the endosperm in the seed is now well established (5,15,17,19,20,21,23,39,40).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis rests on the apparent production of GAlike substances by isolated embryos as shown by bioassay in several experiments (5,12,(18)(19)(20)24) and the suppression of this production by ent-kaurene biosynthesis inhibitors such as CCC and phosphon D (18,20,24). Results from these early experiments on the sites and timing of GA production were conflicting, as were those on the identities and amounts of the GAs formed.…”
mentioning
confidence: 99%
“…Theoretically, GAs biosynthesized during grain development could be stored in the mature grain, either free or conjugated, causing a-amylase induction during germination. However, dry, mature barley embryos generally are reported to have no GA-like activity and no evidence for the release of GAs from conjugates has been found in barley caryopses (1,24).…”
mentioning
confidence: 99%
“…The synthesis of c-amylase and of other hydrolases by the aleurone layers is specifically under the control of gibberellins (8) synthesized in the embryo (13,16,20). What factors control the transport of a-amylase and other hydrolases from the aleurone cells into the starchy endosperm?…”
mentioning
confidence: 99%